The heart of Jacob - Lilymjok, Kyuka (Malthouse Press Limited, 2017)
Jacob prospers as a moneylender and pig merchant by taking advantage of other people's misfortunes. But when he seeks to exploit the famine afflicting his village Tounga by lending money at high interest rates to poor villagers, he does not reckon what a sacrilege his pigs would commit which give the people an opportunity to feast on his own misfortune. When this happens community gives way to individual desires, and the stomach dictates to the head what it should think and believe in. Reason bends to absurdity and custom bows to bizarre novelty. Life explodes into a sinister mess that points to only one outcome: Jacob and society's ultimate ruin.